Non-ischemic Heart Preservation via Hypothermic Cardioplegic Perfusion Induces Immunodepletion of Donor Hearts Resulting in Diminished Graft Infiltration Following Transplantation - Critchley, William R.; Stone, John P.; Liao, Qiuming; Qin, Guangqi; Risnes, Ivar; Trafford, Andrew; Scott, Helge; Sjöberg, Trygve; Steen, Stig; Fildes, James E. (Frontiers in Immunology, 2020)
Introduction: Many donor organs contain significant leukocyte reservoirs which upon transplantation activate recipient leukocytes to initiate acute rejection. We aimed to assess whether non-ischemic heart preservation via ex vivo perfusion promotes immunodepletion and alters the inflammatory status of the donor organ prior to transplantation. Methods: Isolated porcine hearts underwent ex vivo hypothermic, cardioplegic perfusion for 8 h. Leukocyte populations were quantified in left ventricle samples by flow cytometry. Cell-free DNA, cytokines, and chemokines were quantified in the perfusate. Tissue integrity was profiled by targeted proteomics and a histological assessment was performed. Heterotopic transplants comparing ex vivo hypothermic preservation and static cold storage were utilized to assess graft infiltration as a solid clinical endpoint. Results:Ex vivo perfusion significantly immunodepleted myocardial tissue. The perfusate displayed a selective, pro-inflammatory cytokine/chemokine pattern dominated by IFN-γ. The tissue molecular profile was improved following perfusion by diminished expression of nine pro-apoptotic and six ischemia-associated proteins. Histologically, no evidence of tissue damage was observed and cardiac troponin I was low throughout perfusion. Cell-free DNA was detected, the source of which may be necrotic/apoptotic leukocytes. Post-transplant graft infiltration was markedly reduced in terms of both leucocyte distribution and intensity of foci. Conclusions: These findings demonstrate that ex vivo perfusion significantly reduced donor heart immunogenicity via loss of resident leukocytes. Despite the pro-inflammatory cytokine pattern observed, a pro-survival and reduced ischemia-related profile was observed, indicating an improvement in graft viability by perfusion. Diminished graft infiltration was observed in perfused hearts compared with those preserved by static cold storage following 48 h of transplantation.